Gudstjeneste og erkendelse – en Donaldsk analyse af kirkens gudstjenester og deres deltagere - Johansen, Kirstine Helboe; Baunvig, Katrine Frøkjær (Dansk Teologisk Tidsskrift, 2014)
The worship service of the Church has been an object of intense interest within both scholarly work and the everyday work of the congregations. This article contributes to this ongoing discussion by a cognitive analysis of selected services and groups of ritual participants in the Evangelical-Lutheran Church in Denmark. The theoretical framework is the Canadian evolutionary psychologist Merlin Donald. His theory of the evolution of the human cognition is illustrated by a model that guides the analyses of both services and types of ritual participants. The analyses show differences between the cognitive approaches that dominate among the participants and the cognitive appeals that dominate in the ritual procedures. In continuation of these analyses, the conclusion points to cognitive appeals within the ritual procedures of the established church that may be elaborated on to adjust to the group of participants as well as to appeal to the full spectrum of cognitive strategies that any human being possess.